Des colonies à l’Empire fasciste. La conquête de l’Afrique racontée aux enfants italiens - Mariella Colin (Strenae)
In Italy, the conquest and colonization of Africa was inscribed in children’s literature as the territory occupation unfolded, in correspondence with an ideological evolution that accompanied it. In the last decades of the nineteenth century, when liberal Italy began occupying the Horn of Africa, in Eritrea and then in Somalia, this specific colonization found echoes in Salgari’s novels. Likewise, there are texts that celebrate the heroism of fallen soldiers in battle against barbaric and cruel natives, and others that criticize the colonial policy of the state. At the beginning of the 20th century, colonial ambitions seemed to have been put on hold; African adventure novels, written as parody, ridiculed Africans to make young children laugh. Next, the Libyan Invasion (1911-1912) marked a turning point; in works published at the time of the campaign, a new nationalist ideology emerged. After the First World War, the fascists in power wanted to create an Italian "colonial consciousness," associating it with children’s literature. During the Second Italo-Ethiopian War, many stories and novels were published recounting the military campaign in various fictional forms, from stories to novels. These publications presented the Ethiopian conquest as an exciting adventure for Italian children, and colonization as an immense benefit for native children.